Community cohesion in organic waste valorization through composting: The case of the Asentamiento Valle Real Santa Cecilia, La Cruz, Guanacaste (Biocenosis, 2024)
La Cruz, located in the northern Pacific of Costa Rica, is one of the administrative cantons with the lowest social progress index in the country, and Santa Cecilia is one of the less developed districts of this area. Due to the current problem in La Cruz regarding organic waste management, a pilot plan was developed in the Valle Real settlement in Santa Cecilia to reuse organic waste, and generate organic compost, with the aim of subsequently using it in agricultural plantations, and achieving its commercialization in the future. The pilot plan was implemented in 2022 and 2023. A total of three phases were developed: a) initial diagnosis, b) composting, and c) physicochemical analysis of the compost obtained. This pilot plan was launched in a joint effort with the Association of Producers of the Valle Real Settlement, the Guanacaste Campus of the University of Costa Rica and the Municipality of La Cruz. For the development of the pilot plan, this joint work between the municipality and, the academic sector was fundamental, as well as the role of the association and the work of its partners who held key functions. Participatory and ludic methodologies were used to develop the project.
Keywords: organic waste management; composting; compost; community; La Cruz